Estudo da utilização de rejeito de minério de ferro em pavimento de acessos de mina - Débora Dávila Cruz Santos (2024)
Due to the increase in global demand for iron ore especially caused by the expansion of the Chinese market, a decrease in the iron content of products extracted from mines and also changes in Brazilian legislation regarding the use of structures for the disposal of waste, which is the latter influenced by accidents that occurred in Minas Gerais in recent years with the collapse of iron ore mining tailings dams. These factors are the drivers for increasing studies aimed at the use of waste from the mining industry as well as methods for disposing of this waste to meet current regulations. Therefore, mining companies needed to identify uses for this waste preferably with greater value which led to the application of this material, now drier due to filtration processes within the mining itself. Thus, adding to the fact that most mine roads in iron ore complexes are created without any sizing criteria when compared with common traffic highways and that in ore transport a large part of the operating costs include the maintenance of accesses and the operation of off-road trucks closely related to the depreciation of equipment that travels on the roads, it is an opportunity to apply iron ore waste in layers of road pavement structures was observed. This research aims to analyze the geotechnical and structural behavior of iron ore waste applied as infrastructure material for mine roads as well as verify the technical feasibility of applying layers of pavement on mine roads characterize the waste and study the conditions of the ideal pavement composition. The product used for this research known as iron ore tailings was supplied by a multinational mining company in the Iron Quadrangle. Characterization, compaction, CBR and expansion tests were carried out as recommended by Brazilian standards in order to identify the use as layers of a road in accordance with the DNIT Manual (2006). Among them, tests were carried out in addition to those recommended in the manual, such as compaction of the intermediate proctor and the modified proctor. After the analyses among the flexible pavement layers the subgrade and subgrade reinforcement could be identified as compatible for the waste, while the subbase and base did not attest to positive submission, even increasing the compaction energy of the waste material.